Local gyrification index and sulcal depth as imaging markers of cognitive decline in Alzheimer’s disease - Sim, Yongsik; Seo, Changmin; Lee, Young-gun; Ye, Byoung Seok; Lyu, Ilwoo; Sohn, Beomseok (Frontiers in Aging Neuroscience, 2025)
PurposeTo investigate the correlation between cortical thickness (CT), sulcal depth (SD), local gyrification index (LGI), and cognitive scores in patients with Alzheimer’s disease (AD).MethodsA total of 200 patients with AD from 2014 to 2021 were included, confirmed by 18F-florbetaben-positron emission tomography, and having a Clinical Dementia Rating score of 0.5 or 1. Demographic and clinical data were collected, and cognitive function was assessed through the Mini-Mental State Examination (MMSE) and Seoul Neuropsychological Screening Battery (SNSB)-II, with specific z-scores used for multiple divisional cognitive functions. CT, SD, and LGI were extracted from the 3D T1-weighted images acquired with 3-T MRI scanners. General linear models were used to examine associations between cortical features and cognitive scores, controlling for age, sex, and years of education. Cluster-level significance was determined using a family-wise error (FWE)–corrected threshold of p < 0.05, with a cluster-forming height threshold of uncorrected p < 0.01.ResultsThe analysis included patients with a mean age of 73.7 years and an average MMSE score of 23.8. The cortical shape features of multiple brain regions showed significant correlations with the MMSE score after adjusting for age, sex, and years of education. Among those, SD and LGI in the parahippocampal and fusiform gyri had positive correlations with MMSE. For executive function, SD showed correlations in the left inferior frontal and orbitofrontal gyrus. Regarding language function, CT was associated with regions such as the superior temporal gyrus, while SD demonstrated correlations with the left supramarginal gyrus.ConclusionThe results indicate that certain changes in cortical shape features are associated with particular cognitive function scores. Surface-based morphometric features of SD and LGI provided complementary results to CT analyses. Region-specific changes in SD and LGI could be useful imaging markers to predict cognitive decline in AD patients.